Library history of Harbin - A. A. Khisamutdinov (Библиосфера)
The article presents the history of library activities in Harbin which were closely connected with the railway construction in Manchuria. The author analyzes book funds and activity of various types of libraries: those that belonged to the Railway Administration, public organizations, private persons, etc. Special attention is paid to the bibliographic indexes.